Effect of age and parity on maternal diastolic function in middle trimester pregnant women with normal left ventricular ejection fraction and potential link of diastolic function to pre-eclampsia. (25th November 2020) - Zhu, D; Chen, W.Y; Pan, Y.C; Cui, M
Abstract: Background: It has been suggested that maternal cardiac adaptations during pregnancy differ between nulliparous and multipara women and also vary according to the age. Impaired cardiac function precedes pre-eclampsia. Purpose: To evaluate effect of age and parity on maternal cardiac diastolic function in middle trimester among pregnant women with normal left ventricular ejection fraction as well as correlation between impaired diastolic function and pre-eclampsia. Methods: Pregnant women with singleton pregnancies carried from 13 weeks to 20 weeks and left ventricular ejection fraction (LVEF) ≥50% were identified. Diastolic function parameters were assessed using transthoracic echocardiography. Pre-eclampsia was identified from medical records. Results: 376 pregnant women were included (median age: 30 years; median gestational age: 14 weeks; 171 multiparous women). LVEF was 66%. Impaired cardiac diastolic function was seen in 7.8% of pregnant women <35 years compared with 28.6% of those ≥35 years (p=0.000). ROC curve showed women with maternal age over 32 began to have a higher rate of impaired cardiac diastolic function (AUC=0.704, p=0.000, sensitivity=54.5%, specificity=75.3%). There was no difference in diastolic function indices between maternal women grouped by parity. After adjustment for confounders, maternal age can be independent effect factor of Em declined (P<0.05). Em<13cm/s was significantly associated with pre-eclampsia occurrence (HR 8.56; 95% CI: 3.40–21.57) after adjusting for the confounders. Conclusion: Maternal age is an independent impact factor for diastolic function decline. There is no difference in cardiac diastolic function between nullipara and multipara. Pre-eclampsia occurrence is significantly higher in patients with diastolic function decline at mid-gestation. The utility of risk stratification using diastolic function at mid-gestation may improve the survival outcomes of pregnant women. Funding Acknowledgement: Type of funding source: None